Pengaruh Kepuasan Pelanggan Dan Harga Terhadap Keputusan Pembelian Kartu Telkomsel Di Kelurahan Sukomanunggal - Wulandari Wulandari; Iswati Iswati (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
The purpose of this research was to find out and analyze how much influence Customer Satisfaction and price have on customer purchasing decisions in Sukomanunggal Village. This research uses a quantitative method with a descriptive type. Withdrawal of samples using random sampling technique and the number of respondents as many as 100 people. The data analysis method used in this study is multiple regression analysis. The results of this study are that customer satisfaction has a significant and significant effect on Telkomsel card purchasing decisions as seen from the t count > t table (6.367 > 1.661), and a significant level that is lower than 0.05, namely 0.003 > 0.05. price has a significant and significant effect on Telkomsel card purchasing decisions as seen from the value of t count > t table 6.524 > 1.661 and sig 0.000 < 0.05. Customer satisfaction and price have a significant effect on Telkomsel card purchasing decisions as seen from the value of t count > t table f count > f table (108.994 > 3.090 ) and a sig value of 0.000 < 0.05 menas that simultanesously all independent variables have significant and significant effect on the dependent variable.